THE INFLUENCE OF QUALITY OF HEALTH SERVICES ON INPATIENT SATISFACTION AT PANDERE PUBLIC HEALTH CENTER - Iwan, Iwan; Idris, Idris; Santi, Ira Nuriya (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2021)
This research aims to examine and explain the effect of service quality on patient satisfaction at the Pandere Public Health Center, Sigi District. The research method used is explanatory research. The population of this research was all patients who had been treated during 2020, while the sample was 88 respondents. The sampling technique used the Slovin technique. The data analysis method used multiple linear regression with IBM SPSS Statistics version 25 software-assisted. The results of the partial statistical test of service quality variables consisting of Reliability (X1) and Assurance (X3) have a significant positive effect. In comparison, the Responsiveness (X2), Empathy (X4), and Tangible (X5) variables have no significant effect on patient satisfaction. Simultaneous statistical test results show that service quality has a positive and significant effect on patient satisfaction. Keywords: Service Quality, Reliability, Responsiveness, Assurance, Empathy, Tangible, Patient Satisfaction